Modeling of Doped Fully Depleted Behavior Induced by Total Ionizing Dose in Voltage Reference Circuits From a 65-nm Partially Depleted SOI Technology - Lomonaco, J.; Rostand, N.; Martinie, S.; Charbonnier, G.; Marcandella, C.; Bedecarrats, T.; Bournel, A. (IEEE transactions on nuclear science, 2025)
In this article, a doped fully depleted silicon on insulator (FDSOI) behavior for the 65-nm partially depleted silicon on insulator (PDSOI) technology is demonstrated to understand the output voltage shift of a voltage reference (VR) undergoing dose deposition in real time. From an in-depth top-bottom analysis, including both experiments and technology computer aided design (TCAD)/simulation program with integrated circuit emphasis (SPICE) simulations, we highlighted this unexpected doped FDSOI behavior. This study shows how it worsens the total ionizing dose (TID) effects due to the coupling effect between the front and back interfaces, not usual in this technology. A new threshold voltage model considering channel doping and TID is developed, showing how doping concentration is an important hardening parameter. This model is reused, in a multiscale approach, to reproduce the output voltage shift of a VR based on the PDSOI transistor degradation.